Liquid Waste Processing of Tofu Industry for Biomass Production as Raw Material Biodiesel Production. (March 2019) - Widayat, W; Philia, J; Wibisono, J
Abstract: Indonesia as a producer of tofu generated more liquid waste. Nutrients that contained in the tofu wastewater are very useful for the production of microalgae. Chlorella sp. is a microalgae that potential for food supplement, pharmaceuticals, animal feed, aqua culture and cosmetics. Chlorella sp. comonly grow in sea water. Glycerol in the cultivation medium as supplemental organic carbon sources for Microalgae. Cultivation carried out for 9 days at different percentages volume of tofu liquid waste and addition of glycerol. The result showed that increased concentration of tofu waste in microalgae cultivation media is proportional to the increase in lipid levels of Chlorella sp. Variable of 70%V has the highest concentration of lipid. The addition of glycerol in the cultivation medium enchancing lipid production. Variable of 5 g/l glycerol has the highest concentration of lipid. The higher ratio of carbon and nitrogen produces higher lipid content.